PENGARUH FEMALE EXECUTIVE TERHADAP KUALITAS LAPORAN KEUANGAN PADA SEKTOR MANUFAKTURYANG TERDAFTAR DI BEI PERIODE 2012-2014 - Arief Kusumo Atmojo Sugiharto; Felizia Arni Rudiawarni (Akuntansi dan Teknologi Informasi, 2017)
The purpose of this study was to examine the effect of female executives on the quality of financial statements of companies in the manufacturing sector. The quality of the company's financial statements can be seen from the tendency of directors of companies to do the earnings management. The object of this research is manufacturing companies listed in Indonesia Stock Exchange 2012-2014. This study uses a quantitative approach and tested with the regression model. Independent variables used are Female, Leverage, Loss, M / B Ratio, Revenue Growth, Size, SIC and Year. The dependent variable used is Dicretionary Accruals as a proxy of earnings management. The results of this study indicate that the presence of women as an executive in the company turned out to give a good impact for the company, women tend to be more conservative in choosing strategy, particularly related to the financial statements